Prevalence and Demographic Distribution of Adult Survivors of Child Abuse in Japan. (March 2015) - Tsuboi, Satoshi; Yoshida, Honami; Ae, Ryusuke; Kojo, Takao; Nakamura, Yosikazu; Kitamura, Kunio
A cross-sectional study was conducted with a national epidemiological survey to investigate the prevalence and demographic distribution of adult survivors of child abuse in Japan. A self-administered questionnaire was used to measure the history of child abuse and the demographic characteristics. The participants reported the following 4 types of child abuse: physical abuse (3%), sexual abuse (0.6%), neglect (0.8%), and psychological abuse (4%). Significant unequal distribution of child abuse was found to be associated with sex, living region, marital status, job status, and educational status. We determined the prevalence of adult survivors of child abuse in Japan and found that their demographic characteristics were unequally distributed. Policy makers and public health providers should take these demographic disparities into account in considering effective public health interventions for survivors of child abuse.